2018
DOI: 10.2147/ott.s148363
|View full text |Cite
|
Sign up to set email alerts
|

Response to crizotinib in a non-small-cell lung cancer patient harboring an <em>EML4-ALK</em> fusion with an atypical <em>LTBP1</em> insertion

Abstract: Fusion of the anaplastic lymphoma receptor tyrosine kinase gene (ALK) with the echinoderm microtubule-associated protein 4 gene (EML4) is the second most common actionable alteration in non-small-cell lung cancer, with a frequency of 5%. Here, we present a case of an EML4-ALK-positive patient with an atypical in-frame insertion from the LTBP1 gene in the canonical junction of variant 1. The patient was a 39-year-old never-smoker female diagnosed with Stage IV lung adenocarcinoma. A core biopsy was negative for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In our study, a novel LTBP1 ‐ ALK fusion was detected by NGS technology at the baseline specimen of a patient with primary resistance, and his “gold standard” FISH assay result was ALK ‐positive. This fusion gene has not been reported previously, but an EML4‐ALK fusion with atypical LTBP1 insertion could responded well to crizotinib . In future research, we will explore the underlying mechanism for this result.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our study, a novel LTBP1 ‐ ALK fusion was detected by NGS technology at the baseline specimen of a patient with primary resistance, and his “gold standard” FISH assay result was ALK ‐positive. This fusion gene has not been reported previously, but an EML4‐ALK fusion with atypical LTBP1 insertion could responded well to crizotinib . In future research, we will explore the underlying mechanism for this result.…”
Section: Discussionmentioning
confidence: 65%
“…This fusion gene has not been reported previously, but an EML4-ALK fusion with atypical LTBP1 insertion could responded well to crizotinib. 25 In future research, we will explore the underlying mechanism for this result. Because NGS technology has displayed impressive capability for identifying the underlying molecular profile of cancers, its clinical application as a molecular screening test might favorably alter the clinical outcomes of ALK-positive NSCLC patients.…”
Section: Discussionmentioning
confidence: 93%
“…Two reports of lung cancer LTBP1-ALK fusion mutations exist (31,32) (Table 2), and both patients received firstline treatment with crizotinib and reached PR. The kinase domain of ALK is located in exon 20 (4), and the tyrosine kinase domain (exon 20 of ALK) was present in these cases; however, in our case, the LTBP1-ALK occurred in ALK intron 19 (the retained portion was exon 1-19), leaving the kinase domain behind.…”
Section: Discussion Among Physicians From Shandong Cancer Hospital and Institutementioning
confidence: 99%
“…Double-hop fusions can be detected by RNA-seq if their central exons are small enough. A few studies have reported sporadic cases 50 52 . Our discovery and PCR validation of multiple double-hop fusions that underwent canonical splicing establishes the concept of double-hop fusions and indicates that they are prevalent in cancer.…”
Section: Discussionmentioning
confidence: 99%